Sensitivity enhanced refractive index sensor by reducing the influence of in-plane wavevector in photonic spin Hall effect - Sheng, Lijuan (2020)
Photonic spin Hall effect (SHE) can be an effective sensor for determining the refractive index (RI) variation of a sensing medium. How to further improve its sensitivity is a very interesting and important issue. In this paper, we theoretically propose a weak measurement method for enhancing the sensitivity of the photonic SHE-based RI sensor by reducing the influence of the in-plane wavevector. Of particular interest, our results indicate that the sensitivity of the presented configuration reaches about 3.16 × 10-7 RIU/μ m which shows nearly two orders of magnitude improvement compared with the conventional one. Remarkably, this method can be applied for wide range of RI variation of the sensing medium while keeping the high sensitivity.